Severe Isospora (Cystoisospora) belli Diarrhea Preceding the Diagnosis of Human T-Cell-Leukemia-Virus-1-Associated T-Cell Lymphoma. (16th August 2012) - Ud Din, N.; Torka, P.; Hutchison, R. E.; Riddell, S. W.; Wright, J.; Gajra, A.
Abstract : Isospora (Cystoisospora) belli diarrhea can sometimes be fulminant in immunocompromised patients. It is endemic in tropical and subtropical areas, and sporadic episodes have been reported in nonendemic areas in nursing homes, day-care centers, and psychiatric institutions. We describe isosporiasis in an HIV-negative Sudanese-American female who presented with a debilitating diarrheal illness and profound weight loss. Isospora belli was detected in her stool by modified acid-fast staining. Serologic testing was negative for HIV but positive for HTLV-1 infection. Treatment with TMP-SMZ led to improvement in her diarrhea which recurred after stopping antibiotics. Subsequently, she developed generalized lymphadenopathy which was diagnosed as ATLL on immunohistochemical staining. Chemotherapy was initiated, but her condition continued to worsen due to persistent diarrhea and resulting profound electrolyte abnormalities. The patient opted for comfort measures and died a few weeks later at a nursing facility. This case emphasizes that the detection of I. belli should trigger testing for HIV, HTLV-1, and other causes of immunocompromise. We suggest that treatment with TMP-SMZ should be initiated and continued for a prolonged period of time in immunocompromised patients with I. belli diarrhea.